Praktik Pola Asuh dan Status Gizi Anak Balita Usia 6-24 Bulan pada Masyarakat Suku Using Desa Kemiren Kecamatan Glagah, Kabupaten Banyuwangi (The Practice of Parenting Style and Nutritional Status of 6-24 Month-Old Toddlers on Using Community in Kemiren Village, District of Glagah, Banyuwangi Regency) - Fitria Dewi Sri Rahayuningati; Sulistiyani Sulistiyani; Ninna Rohmawati (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Child’s nutritional status was influenced by several factors, including the parenting.Based on the results of weighing operations in February 2014, Kemiren village was inthe fourth highest position of ten villages in Glagah Subdistric for thin and verry thinprevalence. Weighing operations on August 2014 showed that Kemiren was in thesecond highest position of ten villages in, which was 2,94%. Based on teh preliminarystudy, according to midwives and community leaders in Kemiren village, toddlers stillobtained improper parenting, that was, giving food other than breast milk before the ageof 6 months and unvaried food. In addition to nutritional problems, the other underlyingthing was the cultural factors in Kemiren village, one of which was the dietaryrestrictions. There was a presumption among parents that infants should not be givenlady finger bananas because they would experience difficulty in speaking. This studyaimed to identify parenting practice and nutritional status of toddlers aged 6-24 monthsin the community of Using ethnic in Kemiren village.This was a descriptive study usingcross sectional approach. The samples were total population in total of 35 toddlers aged6-24 months. The results of this study showed that most of nutritional parenting were inpoor category, health parenting were in good category, and majority of children hadnormal nutritional status.Keywords: Practice of Parenting, nutritional status